AR Training for Paragliding Pilots: An Investigation of User Experience and Requirements - Köhler, Carolin; Weidner, Florian; Broll, Wolfgang (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2019: Anais do XXI Simpósio de Realidade Virtual e Aumentada, 2019)
This paper addresses the user requirements of implementing augmented reality smart glasses in the paragliding training process aiming to enhance the learning outcomes and safety of pilots. Focusing on improving the thermalling skills of pilots, we developed a prototype application using the Microsoft HoloLens and conducted a field test with six paragliding instructors and ten pilots during a training course in Lusen, South Tyrol, Italy. The exploratory study consisted of testing the device and a prototype at the launching site and semi-structured qualitative interviews. Our results show that integrating AR technology into a pilots helmet would be most beneficial in paragliding training. Users assign great importance to an unrestricted field of view, the simplicity of the user interface and positional accuracy of the virtual elements. The main benefit of the application is that pilots and instructors can share the experience in real-time and that it may enhance their learning outcomes and performance.